High-density ruthenium monatomic and cobalt-ruthenium alloy nanoparticle electro-catalytic material as well as preparation method and application of high-density ruthenium monatomic and cobalt-ruthenium alloy nanoparticle electro-catalytic material
By loading high-density ruthenium single atoms and cobalt ruthenium alloy nanoparticles on the carbon cloth, the problem of single atom agglomeration is solved by using dielectric barrier discharge plasma assistive technology, and the stability and activity of the electrocatalyst is improved, making it suitable for industrial applications.
Patent Information
- Application Number
- CN202411935938.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, when preparing high-density ruthenium single atom and cobalt ruthenium alloy nanoparticle electrocatalysts, single atom agglomeration is difficult to avoid, and the activity and stability of the catalyst are limited.
Carbon cloth is used as the substrate support, and high-density ruthenium single atoms and cobalt ruthenium alloy nanoparticles are loaded through the pyrolysis-ion exchange-pyrolysis method, and with the assistance of dielectric barrier discharge plasma.
It effectively avoids single atom agglomeration, improves the stability and activity of the catalyst, reduces costs, and is suitable for industrial applications.
Smart Images

Figure CN119753740A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis technology, and in particular to an electrocatalytic material of high-density ruthenium single atoms and cobalt-ruthenium alloy nanoparticles with high catalytic activity and stability loaded on carbon fiber, a preparation method thereof, and an application thereof in the electrolysis of water to produce hydrogen and oxygen. Background Art
[0002] With the excessive consumption of traditional fossil fuels and the increasingly serious environmental pollution problem, the research and development of new renewable energy has become one of the hot topics of people's concern. Among the many new energy production devices, water electrolysis, which produces both hydrogen and oxygen, is a very promising and effective way to obtain clean energy. Since the kinetic conversion is slow during the water electrolysis process, a high overpotential needs to be applied to drive the reaction. Therefore, researchers have been committed to developing efficient and feasible water electrolysis catalytic materials to reduce the overpotential of the electrode and thus reduce energy consumption.
[0003] Metal-organic frameworks (MOFs) are porous materials formed by the coordination of metal ions and corresponding organic molecules. Among various MOFs, cobalt-based imidazolide frameworks (ZIF-Co) have been widely studied and used as precursors and self-templates to obtain various nitrogen-doped carbon (NC)-supported cobalt-based electrocatalysts for energy applications. In particular, ZIF-Co-derived cobalt-nitrogen-doped carbon (Co-NC) matrices are widely used to prepare HER electrocatalysts due to their large surface area, excellent conductivity, good stability and low cost. However, the preparation of Co-NC is always accompanied by varying degrees of agglomeration, which greatly limits the performance of the catalyst in the field of hydrogen evolution.
[0004] Related studies have shown that ruthenium (Ru) single-atom catalysts can provide abundant active sites and enhance the activity of the catalyst. Due to its strong adsorption capacity, Ru single atoms can effectively adsorb and activate hydrogen ions (H+) and promote the generation of hydrogen. Especially in high temperature and acidic environments, it can maintain high catalytic activity and durability, making it suitable for industrial applications.
[0005] Therefore, the use of MOF materials and their derivatives to prepare nanoparticles and Ru single-atom electrocatalysts has important research value.
[0006] Although there have been reports on the use of MOF materials to prepare metal nanoparticles and single-atom catalysts, due to the special nature of MOF materials that often require pyrolysis during the preparation process, traditional pyrolysis strategies are usually accompanied by the aggregation of single atoms, making it difficult to achieve high-density single-atom loading to meet the needs of industrial electrocatalysts. Therefore, it is necessary to explore a new method for preparing high-density, stable catalytic activity for actual water splitting.
[0007] Plasma is the fourth state of matter alongside solid, liquid and gas, and has many advantages in electrocatalyst engineering, such as improving the interface coupling between the catalyst and the catalytic support material, achieving effective heteroatom doping at lower temperatures, etc. In addition, the "thermal shock" effect of plasma can create defect sites that capture atoms, greatly limiting the aggregation of single atoms, which makes it possible to prepare higher-density single-atom catalysts.
[0008] Therefore, it is of great research significance to develop a preparation method for high-density ruthenium single atoms and cobalt-ruthenium alloy nanoparticle catalysts in combination with plasma technology, which may open up a new research field for promoting clean H2 energy technology. Summary of the invention
[0009] The present invention provides a method for preparing high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic materials with carbon cloth (CC) as a matrix support. The electrocatalytic material of the present invention is prepared by pyrolysis-ion exchange-pyrolysis under the assistance of dielectric barrier discharge (DBD) plasma. The present invention can not only effectively solve the problem of easy agglomeration of single atoms in the traditional pyrolysis process, but also reduce costs, improve the stability and catalytic activity of electrode materials, and has great industrial and practical application value.
[0010] A method for preparing a high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material, using carbon cloth (CC) as a substrate to grow a MOF material ZIF-Co, through pyrolysis and with the assistance of dielectric barrier discharge (DBD) plasma, so that it can load more Ru during ion exchange, and finally through pyrolysis reduction, high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrode catalytic material can still be obtained. In the preparation method of the present invention, the dielectric barrier discharge plasma treatment not only improves the stability of the electrocatalyst, but also avoids the problem of large-scale agglomeration of single atoms caused by the traditional pyrolysis method.
[0011] The present invention provides a method for preparing high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalysts with superior electrocatalytic performance, strong stability and environmental friendliness. The present invention fills the gap in the application of plasma in the preparation of high-density single atom and alloy nanoparticle electrocatalysts, and has great potential application value in oxygen evolution reaction and hydrogen evolution reaction.
[0012] A method for preparing high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material, comprising:
[0013] Step 1: immerse the carbon cloth in a mixed solution containing 2-methylimidazole and cobalt (II) nitrate to grow ZIF-Co nanosheets on the carbon cloth, then take out the carbon cloth, wash it, and dry it to obtain ZIF-Co / CC;
[0014] Step 2: pyrolyzing ZIF-Co / CC under an inert atmosphere to obtain cobalt-nitrogen doped carbon;
[0015] Step 3, subjecting the cobalt-nitrogen doped carbon to dielectric barrier discharge plasma treatment, and then subjecting the carbon to ion exchange with a ruthenium (III) source;
[0016] Step 4: Pyrolyze the ion exchange product of step 3 under the protection of an inert atmosphere to obtain the high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material.
[0017] In step 1, the mass ratio of cobalt (II) in cobalt (II) nitrate to 2-methylimidazole may be (0.02-0.17):(0.5-2.0).
[0018] In step 1, the ratio of the mass of cobalt (II) in cobalt (II) nitrate to the single-side area of the carbon cloth can be (0.02-0.17) g:4 cm 2 .
[0019] In step 1, the time for growing ZIF-Co nanosheets on the carbon cloth can be 2 to 8 hours.
[0020] In step 2, the inert atmosphere refers to a gas atmosphere that does not participate in the reaction, and specifically may include a rare gas atmosphere and / or a nitrogen atmosphere.
[0021] In step 2, the pyrolysis temperature may be 400-900°C.
[0022] In step 2, the pyrolysis time may be 30 to 120 minutes.
[0023] In step 2, the heating rate of the pyrolysis can be 2 to 8°C / min.
[0024] In step three, the dielectric barrier discharge plasma treatment time is preferably 10 to 30 minutes, for example, 15 minutes, 20 minutes, 25 minutes, etc.
[0025] In step three, the voltage of the dielectric barrier discharge plasma treatment can be 5-30 kV, further can be 10-30 kV, for example, 20 kV, etc., the frequency can be 10-80 kHz, further can be 10-30 kHz, for example, 20 kHz, etc., the power can be 50-100 W, for example, 60 W, etc.
[0026] In step three, the thickness of the dielectric layer treated by dielectric barrier discharge plasma can be 1-5 mm, further 1-2 mm, such as 2 mm, etc. Flat plate discharge can be used, and the discharge gap can be 2-8 mm, further 3-4 mm, such as 4 mm, etc.
[0027] In step three, the medium used in the dielectric barrier discharge plasma treatment may be quartz.
[0028] In step 3, the mass ratio of ruthenium (III) in the ruthenium (III) source to cobalt (II) in cobalt (II) nitrate can be (2-15):(20-170).
[0029] In step 3, the ruthenium (III) source may include RuCl 3 or the like.
[0030] In step three, a ruthenium (III) source can be ion exchanged with the cobalt-nitrogen doped carbon after dielectric barrier discharge plasma treatment in the form of a solution.
[0031] In step 3, the ion exchange time can be 10 to 80 minutes.
[0032] In step 4, the inert atmosphere refers to a gas atmosphere that does not participate in the reaction, and specifically may include a rare gas atmosphere and / or a nitrogen atmosphere.
[0033] In step 4, the pyrolysis temperature may be 400-900°C.
[0034] In step 4, the pyrolysis time may be 30 to 120 minutes.
[0035] In step 4, the heating rate of the pyrolysis can be 2 to 8°C / min.
[0036] The present invention further provides high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic materials prepared by the preparation method.
[0037] The present invention also provides the use of the high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material in the electrolysis of water to produce hydrogen and oxygen.
[0038] In current technology, the process of preparing nanoparticles and single-atom catalysts using MOF materials is mostly pyrolysis synthesis, and it is difficult to simultaneously obtain high-density metal single atoms and alloy nanoparticles. The present invention cleverly uses dielectric barrier discharge plasma to create defect sites on the surface of the material that can capture atoms, greatly inhibiting the agglomeration of Ru single atoms. Not only cobalt-ruthenium alloy nanoparticles are loaded on the carbon cloth, but also high-density Ru single atoms are formed, which not only improves the catalytic performance, conductivity and stability of the electrocatalyst, but also greatly improves the corrosion resistance of the catalyst. The prepared high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalyst further improves the electrocatalytic performance of the material.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The present invention proposes a dielectric barrier discharge plasma chemically assisted preparation of high-density ruthenium single atoms and cobalt-ruthenium alloy nanoparticle electrocatalysts. The prepared high-density ruthenium single atoms and cobalt-ruthenium alloy nanoparticle electrocatalysts are uniformly coated on carbon fibers, and at the same time have high-density ruthenium single atoms and cobalt-ruthenium alloy nanoparticles. The catalyst has excellent electrocatalytic performance. Compared with the catalyst formed by the agglomeration of metal single atoms in the traditional preparation method, the catalyst has the characteristics of ultra-large active surface area, abundant active centers and rapid electron transfer, thereby ensuring that its performance under high current density and industrial related conditions is better than other precious metal catalysts. Its material properties, structure and novelty of preparation ideas have not been reported in the literature. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The present invention is a schematic flow chart of a method for preparing high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic materials.
[0042] Figure 2 This is a scanning electron microscope photograph of the high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle catalyst (RuCo-NC-PT / CC-2) in Example 2.
[0043] Figure 3 This is a transmission electron microscope photo of the high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle catalyst (RuCo-NC-PT / CC-2) in Example 2.
[0044] Figure 4 This is a spherical aberration corrected transmission electron microscope photograph of the high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle catalyst (RuCo-NC-PT / CC-2) in Example 2.
[0045] Figure 5 This is a spherical aberration corrected transmission electron microscope photograph of the catalyst (RuCo-NC-T / CC) prepared in Comparative Example 3 without the use of dielectric barrier discharge plasma to assist in preparation.
[0046] Figure 6 The hydrogen evolution polarization curves are of the high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle catalysts in Examples 1 to 2, the Co-NC / CC prepared in Comparative Example 1, the catalyst Co-NC-P / CC obtained by treating Co-NC / CC with dielectric barrier discharge plasma in Comparative Example 2, the catalyst RuCo-NC-T / CC prepared without dielectric barrier discharge plasma treatment in Comparative Example 3, and the Pt / C / CC catalyst in Comparative Example 4.
[0047] Figure 7 It is the hydrogen evolution polarization curve diagram of the catalyst of Examples 3 to 6. DETAILED DESCRIPTION
[0048] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0049] Embodiment 1:
[0050] See also Figure 1 , a method for preparing high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material, comprising:
[0051] Step 1: Dissolve 0.5 g of 2-methylimidazole (2-MeIM) and 100 mg of cobalt nitrate hexahydrate in deionized water respectively, and stir on a stirrer for 2 min; then mix the two solutions to form a purple turbid liquid, immerse a 2 cm × 2 cm carbon cloth in the mixed solution for 2 h to grow ZIF-Co nanosheets; finally, wash with deionized water and dry in an oven to obtain ZIF-Co / CC;
[0052] Step 2: In a tube furnace, place the ZIF-Co / CC obtained in step 1 into a quartz boat and introduce nitrogen at 2°C min -1 The temperature was raised from room temperature to 400°C, the pyrolysis time was 30 min, and after the pyrolysis was completed, it was naturally cooled to 25°C to obtain cobalt-nitrogen doped carbon Co-NC / CC.
[0053] Step 3: Turn on the dielectric barrier discharge device, adjust the pretreatment power to 50W, and perform preheating. After the preheating is completed, put the cobalt-nitrogen-doped carbon Co-NC / CC obtained in step 2 between two disc electrodes in the dielectric barrier discharge device, with a voltage of 20kV, a frequency of 20KHz, a quartz dielectric layer thickness of 2mm, a flat plate discharge gap of 4mm, and adjust the plasma discharge treatment power to 50W, and the plasma discharge time to 10min to obtain the catalyst Co-NC-P / CC. Then put the treated catalyst Co-NC-P / CC into a RuCl3 solution containing 5mg RuCl3 for ion exchange, and the ion exchange time is 20min.
[0054] Step 4: In a tube furnace, place the catalyst obtained in step 3 into a quartz boat and introduce nitrogen at 2°C min -1 The temperature was raised from room temperature to 400°C, the pyrolysis time was 30 minutes, and after the pyrolysis was completed, it was naturally cooled to 25°C to obtain a high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalyst (RuCo-NC-PT / CC-1) loaded on carbon cloth.
[0055] Embodiment 2:
[0056] See also Figure 1 , a method for preparing high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material, comprising:
[0057] Step 1: Dissolve 1.5 g of 2-methylimidazole and 200 mg of cobalt nitrate hexahydrate in deionized water respectively, and stir on a stirrer for 3 min; then mix the two solutions to form a purple turbid liquid, immerse a 2 cm × 2 cm carbon cloth in the mixed solution for 4 h to grow ZIF-Co nanosheets; finally, wash with deionized water and dry in an oven to obtain ZIF-Co / CC;
[0058] Step 2: In a tube furnace, place the ZIF-Co / CC obtained in step 1 into a quartz boat and introduce nitrogen at 2°C min -1 The temperature was raised from room temperature to 900°C, the pyrolysis time was 30 min, and after the pyrolysis was completed, it was naturally cooled to 25°C to obtain cobalt-nitrogen doped carbon Co-NC / CC.
[0059] Step 3: Turn on the dielectric barrier discharge device, adjust the pretreatment power to 60W, and perform preheating. After the preheating is completed, put the cobalt-nitrogen-doped carbon Co-NC / CC obtained in step 2 between two disc electrodes in the dielectric barrier discharge device, with a voltage of 20kV, a frequency of 20KHz, a quartz dielectric layer thickness of 2mm, a flat plate discharge gap of 4mm, and adjust the plasma discharge treatment power to 60W, and the plasma discharge time to 20min to obtain the catalyst Co-NC-P / CC. Then put the treated catalyst Co-NC-P / CC into a RuCl3 solution containing 10mg RuCl3 for ion exchange, and the ion exchange time is 30min.
[0060] Step 4: In a tube furnace, place the catalyst obtained in step 3 into a quartz boat and introduce nitrogen at 2°C min -1 The temperature was raised from room temperature to 900°C, the pyrolysis time was 30 minutes, and after the pyrolysis was completed, it was naturally cooled to 25°C to obtain a high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalyst (RuCo-NC-PT / CC-2) loaded on carbon cloth.
[0061] In order to further explore the effect of dielectric barrier discharge plasma on catalyst performance, the performance of Examples 3 to 6 was compared.
[0062] Embodiment 3:
[0063] Step 1: Dissolve 1.8 g of 2-methylimidazole and 400 mg of cobalt nitrate hexahydrate in deionized water respectively, and stir on a stirrer for 3 min; then mix the two solutions to form a purple turbid liquid, immerse a 2 cm × 2 cm carbon cloth in the mixed solution for 5 h to grow ZIF-Co nanosheets; finally, wash with deionized water and dry in an oven to obtain ZIF-Co / CC;
[0064] Step 2: In a tube furnace, place the ZIF-Co / CC obtained in step 1 into a quartz boat and introduce nitrogen at 5°C min -1 The temperature was raised from room temperature to 900°C, the pyrolysis time was 60 min, and after the pyrolysis was completed, it was naturally cooled to 25°C to obtain cobalt-nitrogen doped carbon Co-NC / CC.
[0065] Step 3: Place the obtained catalyst Co-NC / CC into a RuCl3 solution containing 10 mg RuCl3 for ion exchange. The ion exchange time is 30 min.
[0066] Step 4: In a tube furnace, place the catalyst obtained in step 3 into a quartz boat and introduce nitrogen at 2°C min -1 The temperature was raised from room temperature to 900°C, the pyrolysis time was 60 min, and after the pyrolysis was completed, it was naturally cooled to 25°C to obtain the catalyst (RuCo-NC-T / CC-0min).
[0067] Embodiment 4:
[0068] See also Figure 1 , a method for preparing high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material, comprising:
[0069] Step 1: Dissolve 1.8 g of 2-methylimidazole and 400 mg of cobalt nitrate hexahydrate in deionized water respectively, and stir on a stirrer for 3 min; then mix the two solutions to form a purple turbid liquid, immerse a 2 cm × 2 cm carbon cloth in the mixed solution for 5 h to grow ZIF-Co nanosheets; finally, wash with deionized water and dry in an oven to obtain ZIF-Co / CC;
[0070] Step 2: In a tube furnace, place the ZIF-Co / CC obtained in step 1 into a quartz boat and introduce nitrogen at 5°C min -1 The temperature was raised from room temperature to 900°C, the pyrolysis time was 60 min, and after the pyrolysis was completed, it was naturally cooled to 25°C to obtain cobalt-nitrogen doped carbon Co-NC / CC.
[0071] Step 3: Turn on the dielectric barrier discharge device, adjust the pretreatment power to 50W, and perform preheating. After the preheating is completed, put the cobalt-nitrogen-doped carbon Co-NC / CC obtained in step 2 between two disc electrodes in the dielectric barrier discharge device, with a voltage of 20kV, a frequency of 20KHz, a quartz dielectric layer thickness of 2mm, a flat plate discharge gap of 4mm, and adjust the plasma discharge treatment power to 50W, and the plasma discharge time to 15min to obtain the catalyst Co-NC-P / CC. Then put the treated catalyst Co-NC-P / CC into a RuCl3 solution containing 10mg RuCl3 for ion exchange, and the ion exchange time is 30min.
[0072] Step 4: In a tube furnace, place the catalyst obtained in step 3 into a quartz boat and introduce nitrogen at 2°C min -1 The temperature was raised from room temperature to 900°C, the pyrolysis time was 60 min, and after the pyrolysis was completed, it was naturally cooled to 25°C to obtain the catalyst (RuCo-NC-PT / CC-15min).
[0073] Embodiment 5:
[0074] The only difference from Example 4 is that in step 3, the dielectric barrier discharge plasma treatment time is changed to 25 min, and the other conditions are the same, and the corresponding catalyst RuCo-NC-T / CC-25min is obtained.
[0075] Embodiment 6:
[0076] The only difference from Example 4 is that in step 3, the dielectric barrier discharge plasma treatment time is changed to 35 min, and the other conditions are the same, and the corresponding catalyst RuCo-NC-T / CC-35min is obtained.
[0077] Comparative Example 1:
[0078] The difference from Example 2 is that there are no steps three and four, that is, the cobalt-nitrogen doped carbon Co-NC / CC is obtained on the carbon cloth by only one-step pyrolysis method, and the other conditions are the same.
[0079] Comparative Example 2:
[0080] The difference from Example 2 is that there is no ion exchange in step three and no step four, and the cobalt-nitrogen doped carbon Co-NC / CC is obtained on carbon cloth by a one-step pyrolysis method, and then a dielectric barrier discharge treatment is performed to obtain the corresponding catalyst Co-NC-P / CC, and the other conditions are the same.
[0081] Comparative Example 3:
[0082] The only difference from Example 2 is that the dielectric barrier discharge plasma treatment in step 3 is omitted, and the other conditions are the same to obtain the corresponding catalyst RuCo-NC-T / CC.
[0083] Comparative Example 4:
[0084] The preparation method of Pt / C / carbon cloth catalyst (abbreviated as Pt / C / CC or Pt / C / CC catalyst) is similar to the preparation method of Pt / C / CC electrodes disclosed in In-situ growth of ruthenium-based nanostructure on carbon cloth for superior electrocatalytic activity towards HER and OER (DOI:10.1016 / j.apcatb.2022.121729).
[0085] Through examples, comparative examples, combined Figures 2 to 7 And the analysis of Table 1 is as follows:
[0086] Figure 2 It shows that the catalyst presents a coating structure on the carbon cloth, and due to the influence of dielectric barrier discharge, defects of varying degrees appear on the surface of the catalyst, which increases the electrocatalytic reaction area and improves the activity and stability of the catalyst.
[0087] Figure 3 , Figure 4 The distribution of catalyst cobalt-ruthenium alloy nanoparticles and high-density ruthenium single atoms is shown, which provides abundant active sites for the catalyst and enhances the activity of the catalyst.
[0088] Figure 5 It shows that the prepared catalyst contains only a small number of single atoms because dielectric barrier discharge plasma treatment was not used.
[0089] Figure 6 Table 1 shows the test of hydrogen evolution performance of different catalysts using a three-electrode system in a 1.0 M potassium hydroxide solution, including the high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle catalysts (302 mV, 283 mV) in Examples 1-2, Co-NC / CC prepared in Comparative Example 1 (603 mV), the catalyst Co-NC-P / CC obtained by dielectric barrier discharge plasma treatment of Co-NC / CC in Comparative Example 2 (582 mV), the catalyst RuCo-NC-T / CC prepared without dielectric barrier discharge plasma treatment in Comparative Example 3 (405 mV), and the Pt / C / CC catalyst in Comparative Example 4 (517 mV) at a current density of 1000 mA cm -2 The overpotential value of the hydrogen evolution reaction.
[0090] Figure 7 Table 2 shows the test of hydrogen evolution performance of different catalysts using a three-electrode system in a 1.0 M potassium hydroxide solution, including the catalyst performance at a current density of 1000 mA cm under dielectric barrier discharge plasma treatment for different time periods in Examples 3 to 6.-2 The overpotential value of the hydrogen evolution reaction.
[0091] Table 1 shows the high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle catalysts in Examples 1-2, Co-NC / CC prepared in Comparative Example 1, Co-NC-P / CC obtained by dielectric barrier discharge plasma treatment of Co-NC / CC in Comparative Example 2, RuCo-NC-T / CC prepared without dielectric barrier discharge plasma treatment in Comparative Example 3, and Pt / C / CC catalyst in Comparative Example 4 at a current density of 1000 mA cm -2 The overpotential value of the hydrogen evolution reaction.
[0092] Table 2 shows the catalysts prepared by using dielectric barrier discharge plasma treatment for different time periods in Examples 3 to 6 at a current density of 1000 mA cm -2 The overpotential value of the hydrogen evolution reaction.
[0093] Table 1
[0094]
[0095] Table 2
[0096]
[0097] After the cobalt-nitrogen doped carbon of Comparative Example 1 was treated with dielectric barrier discharge plasma, the overpotential was reduced from 603mV to 582mV (Comparative Example 2), which was only reduced by 21mV, indicating that the dielectric barrier discharge plasma treatment has a certain electrochemical performance improvement effect on the cobalt-nitrogen doped carbon system without Ru, but it is not particularly significant. When Ru ion exchange and secondary pyrolysis are introduced, the effect of dielectric barrier discharge plasma treatment on the electrochemical performance of the catalyst is very significant. For example, the overpotential of the RuCo-NC-T / CC catalyst without dielectric barrier discharge plasma treatment in Comparative Example 3 is 405mV, while the overpotential of the RuCo-NC-PT / CC-2 catalyst treated with dielectric barrier discharge plasma in Example 2 is as low as 283mV, which is a significant decrease of 122mV, indicating that the dielectric barrier discharge plasma treatment plays an unexpectedly important role in improving the electrocatalytic performance of the catalyst in the pyrolysis-ion exchange-pyrolysis preparation route of the present invention.
[0098] Examples 3 to 6 show the effect of dielectric barrier discharge plasma on catalyst performance at different treatment times. As the treatment time increases, the performance gradually improves. The reason for the decrease in catalyst performance after 35 minutes of treatment may be that the long-term treatment caused a certain degree of damage to the carbon fiber substrate. It can be seen that the dielectric barrier discharge plasma treatment catalyst should be controlled within a reasonable range.
[0099] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material, characterized in that: include: Step 1: immerse the carbon cloth in a mixed solution containing 2-methylimidazole and cobalt (II) nitrate to grow ZIF-Co nanosheets on the carbon cloth, then take out the carbon cloth, wash it, and dry it to obtain ZIF-Co / CC; Step 2: pyrolyzing ZIF-Co / CC under an inert atmosphere to obtain cobalt-nitrogen doped carbon; Step 3: subjecting the cobalt-nitrogen doped carbon to dielectric barrier discharge plasma treatment, and then subjecting it to ion exchange with a ruthenium (III) source; the dielectric barrier discharge plasma treatment time is 10 to 30 minutes; Step 4: Pyrolyze the ion exchange product of step 3 under the protection of an inert atmosphere to obtain the high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material.
2. The preparation method according to claim 1, characterized in that: In step one: The mass ratio of cobalt (II) to 2-methylimidazole in cobalt (II) nitrate is (0.02-0.17):(0.5-2.0); The ratio of the mass of cobalt (II) in cobalt (II) nitrate to the single surface area of carbon cloth is (0.02-0.17) g:4 cm 2 ; The time for growing ZIF-Co nanosheets on carbon cloth is 2 to 8 hours.
3. The preparation method according to claim 1, characterized in that: In step 2: The inert atmosphere includes a rare gas atmosphere and / or a nitrogen atmosphere; The pyrolysis temperature is 400-900°C; The pyrolysis time is 30 to 120 minutes; The heating rate of the pyrolysis is 2-8°C / min.
4. The preparation method according to claim 1, characterized in that: In step three: The voltage of dielectric barrier discharge plasma treatment is 5-30 kV, the frequency is 10-80 kHz, and the power is 50-100 W; The thickness of the dielectric layer treated by dielectric barrier discharge plasma is 1 to 5 mm, flat plate discharge is used, and the discharge gap is 2 to 8 mm; The medium used in dielectric barrier discharge plasma treatment is quartz.
5. The preparation method according to claim 4, characterized in that: In step three: The voltage of dielectric barrier discharge plasma treatment is 10 to 30 kV and the frequency is 10 to 30 kHz; The thickness of the dielectric layer treated by dielectric barrier discharge plasma is 1 to 2 mm, and the discharge gap is 3 to 4 mm.
6. The preparation method according to claim 1, characterized in that: In step three: The mass ratio of ruthenium (III) in the ruthenium (III) source to cobalt (II) in the cobalt (II) nitrate is (2-15):(20-170); The ruthenium (III) source includes RuCl3; A ruthenium (III) source in solution is ion exchanged with cobalt-nitrogen-doped carbon treated with dielectric barrier discharge plasma; The ion exchange time is 10 to 80 minutes.
7. The preparation method according to claim 1, characterized in that: In step 4: The inert atmosphere includes a rare gas atmosphere and / or a nitrogen atmosphere; The pyrolysis temperature is 400-900°C; The pyrolysis time is 30 to 120 minutes; The heating rate of the pyrolysis is 2-8°C / min.
8. High-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the high-density ruthenium single atom and cobalt-ruthenium alloy nanoparticle electrocatalytic material according to claim 8 in the electrolysis of water to produce hydrogen and oxygen.